HUBUNGAN SELF-MANAGEMENT DENGAN KUALITAS HIDUP LANSIA HIPERTENSI - Utami, Gusti Nyoman Mega; Widyanthari, Desak Made; Suarningsih, Ni Kadek Ayu (Coping: Community of Publishing in Nursing; Vol 9 No 6 (2021): Desember 2021, 2021)
Hypertension is a chronic disease that often occurs in elderly. Increased blood pressure in hypertension will have an impact on decreasing life quality of the elderly. Self-management plays an important role in controlling blood pressure to prevent further symptoms and complications. This study intended to define the relationship among self-management and life quality of elderly with hypertension in the working area of ??Buleleng I Public Health Center. This study was a correlative study with a cross-sectional design on 30 elderly with hypertension selected through consecutive sampling technique. The research instruments used were  Hypertension Self-Management Behavior Questionnaire and Older People's Quality of Life questionnaire. The results indicated the average score of self-management and quality of life of the elderly were in good category. The results of the Spearman Rank test showed statistically there was a positive and very strong relationship among self-management and the quality of life of the elderly with hypertension in the working area of ??the Buleleng I Public Health Center (p = 0,000; r = 0,810). Elderly with hypertension were expected to improve self-management through the implementation of a healthy lifestyle and regular medical check up to the health services to improve life quality.